TYPOLOGYCAL VARIETIES OF STRATEGIES IN SOCIAL MEDIA - Victoria Ivashchenko; Mykhailo Hryshyn (Інтегровані комунікації)
An analytical review of Ukrainian and foreign literature on the study of manipulative technologies (strategies and tools) in social media was carried out. Observations are summarized and systematized by research objects and problems. The variety of communicative strategies observable in today’s social media underscores the relevance of the chosen problem, particularly the distinction between "manipulative strategies"and "anti-manipulation strategies". This paper partially examines concepts such as "manipulative technologies", "manipulative strategies", "manipulation subject", "manipulation object", and "manipulation tools". It was found that the concepts of "anti-manipulation" and "anti-manipulation strategy" in the communicative aspect have not yet been developed in scientific works. Using an information search method, the study selected relevant scientific literature focused onmanipulative strategies (1) and anti-manipulation strategies (2), in particular in social media. Through problem analysis, the main types of these strategies were identified. The descriptive method allowed for a detailed exploration of their characteristics. Given the military-political context, the paper analyzes key varieties of strategies: (1) disinformation strategies, propaganda strategies that create alternative realities, information operation strategies utilizing bots, doxing strategies, strategies for factual manipulation, ideological polarization strategies, and strategies that evade the truth and distort information, strategy "neglect, distort, distract, discourage"; (2) strategies for countering disinformation (strategy of technological solutions, development of media literacy, state and international initiatives), strategy of information security. In conclusion, it is noted that manipulative technologies encompass a wide range of strategies, while the strategies of countering manipulations still require further theoretical development typological classification.